Reduce the equation of straight line 2x+3y = 12 in double intercept form and hence mention its X-intercept and Y-intercept.​

Answers

Answer 1
Answer:

Answer:

x intercept: (x,0)

y intercept: (0,y)

2x+0=12/÷2 0+3y=12/÷3

x=6 y=4

(x)/(a)  +  (y)/(b)  = 1 \n

(x)/(6)  +  (y)/(4)  = 1


Related Questions

The difference of a number and thirty-six is seven. Algebraic expression
Sarah put raisins into 3/4 of the oatmeal cookie dough she was making. She put nuts into 2/5 of the oatmeal cookie dough with the raisins. What fraction of the entire batch has BOTH raisins and nuts.
Three restaurants sell turkey sandwiches in a small town: Delicious Deli, Garden Fresh, and Uptown Eatery.Delicious Deli sells 5 turkey sandwiches for $20.00.Garden Fresh sells 2 turkey sandwiches for $8.50.Uptown Eatery sells 3 turkey sandwiches for $13.50. The graph shows Delicious Deli’s turkey sandwich sales, where x represents the number of turkey sandwiches sold, and y represents the total cost.
Help on gradpoint!!!
Which Of These Equations Is Equivalent To 6 3/3 x 3 1/4 = 19? A. 3 1/4 ÷ 19 = 6 3/4 B. 19 ÷ 3 1/4 = 6 3/4 C. 3 1/4 ÷ 6 3/4 = 19 D. 6 3/4 ÷ 3 1/4 = 19

2 step equation that equals 10

Answers

Equation compares two expressions. A 2 step equation that is equal to 10 can be (x+1)5=10.

What are equations?

An equation is a pair of two expressions that are compared with the help of an equal sign. '='.

There are a lot of possible 2 step equations that are equal to 10. for example,

  • 5x=10
  • (x+1)5=10

Hence, A 2 step equation that is equal to 10 can be (x+1)5=10.

Learn more about Equation:

brainly.com/question/2263981

35- 5 x 5Order of operations, 5 x 5= 25. 35-25=10

Simplify the expression 6ab + 3ab - 7ab. What is the coefficient of the simplified expression?A. a
B. ab
C. 2
D. b

Answers

Simplifying 6ab + 3ab - 7ab
so we can write it 
6ab + 3ab - 7ab = 0 ( because there is nothing on right side ) 
9ab - 7ab = 0
2ab = 0
So the coefficient of ab is 2.

Correct option is C.
To simply to expression 6ab+3ab-7ab, we do:
6ab+3ab-7ab+= (Just do regular addition and subtraction if they have the same coefficent)
9ab-7ab=
2ab
So the answer is C.

A PS4 uses 8.8 watts when on stand-by mode. How much electricity would be used if you have your PS4 on stand-by 21 hours a day for 2 weeks?

Answers

2 weeks = 14 days. 
21 hours × 14 days = 294 hours total.

8.8 watts × 294 hours = 2587.2 Wh or 2.5872 kWh. 

Determine whether (6,4) is a solution of y = 19x - 2.

Answers

Answer:

Not a solution

Step-by-step explanation:

To determine if a pair of coordinates is the solution to an equation, just plug it in.

Given that the equation is:

y = 19x - 2

And the coordinates they give us to evaluate:

(6, 4)

Plug the coordinates in:

y = 19x - 2

4 = 19(6) - 2

4 = 114 - 2

4 = 112

4 ≠ 112

4 is not equal to 112. Therefore this pair is not the solution.

Answer:  No, it's not a solution.

Explanation

The point (6,4) tells us that x = 6 and y = 4 pair up together.

Plug those values into the equation. Simplify both sides as much as possible (use PEMDAS). If we get the same thing on both sides, then that point is a solution to the equation.

y = 19x - 2

4 = 19*6 - 2

4 = 114 - 2

4 = 112

We get different values on each side. Therefore, the point (6,4) is not a solution to the equation.

Another approach you could do is graph the equation using a tool like Desmos. GeoGebra works as well. The point (6,4) is not on the diagonal line. Check out the diagram below to see what I mean.

Use the distributive Property to evaluate the expression
(-12) (6 + 4)

Answers

Answer:

Step-by-step explanation:

if we use the distributive Property to evaluate the expression it will be

-12(6+4)

-12*6=-72

-12*4=-42

now we add both of them (-72+-42 is -120)

(3x+1)(2x-5)=39
i need help

Answers

(3x+1)(2x-5)=39 \n6x^2-15x+2x-5=39 \n6x^2-13x-5=39 \ \ \ \ \ \ \ \ \ \ |-39 \n6x^2-13x-44=0 \n6x^2-24x+11x-44=0 \n6x(x-4)+11(x-4)=0 \n(6x+11)(x-4)=0 \n6x+11=0 \ \lor \ x-4=0 \n6x=-11 \ \lor \ x=4 \nx=-(11)/(6) \ \lor \ x=4 \n\boxed{x=-1 (5)/(6) \hbox{ or } x=4}
                       (3x + 1)(2x - 5) = 39
              3x(2x - 5) + 1(2x - 5) = 39
3x(2x) + 3x(-5) + 1(2x) + 1(-5) = 39
          6x² + (-15x) + 2x + (-5) = 39
                  6x² - 15x + 2x - 5 = 39
                          6x² - 13x - 5 = 39
                                        - 39 - 39
                        6x² - 13x - 44 = 0
                                            x = -(-13) ± √((-13)² - 4(6)(-44))
                                                                    2(6)
                                            x = 13 ± √(169 + 1056)
                                                               12
                                            x = 13 ± √(1225)
                                                       12
                                            x = 13 ± 35
                                                      12
                                            x = 13 + 35    ∨    x = 13 - 35
                                                      12                         12
                                            x = 48        ∨        x = -22
                                                  12                         12
                                            x = 4         ∨         x = -1⁵/₆
The solution set us equal to {4, -1⁵/₆}.